Atlantic to Pacific: Outbreak of bivalve transmissible neoplasia detected in hybridizing soft-shell clams and eDNA in Puget Sound - Sydney A. Weinandt; Zachary J. Child; Dorothy Lartey; Angel Santos; Holden Maxfield; Jordana K. Sevigny; Fiona E. S. Garrett; Peter D. Smith; Rachael M. Giersch; Samuel F. M. Hart; Lucas Rabins; Samuel Kaiser; et al. (Proceedings of the National Academy of Sciences, 2026)
Bivalve transmissible neoplasias (BTNs) are transmissible cancers that have arisen in multiple bivalve species, including Eastern soft-shell clam ( Mya arenaria ) populations on the East Coast of North America. Two sublineages of a single clone (termed MarBTN) currently circulate at low enzootic levels (1 to 5%) in New England, the United States, and Prince Edward Island, Canada, but MarBTN has not previously been observed in soft-shell clams on the West Coast. In 2022, we collected soft-shell clams in Puget Sound, Washington, and unexpectedly found MarBTN in two sites. Prevalence increased in subsequent years, surpassing 75% at both sites in 2024, while remaining undetectable in other populations, suggesting the early stages of a severe disease outbreak. Based on the presence of somatic transposon insertion sites found only in the USA-sublineage, the cancer was likely recently transplanted from New England. We also found that soft-shell clams in multiple Puget Sound locations are hybridizing populations of M. arenaria and Mya japonica . M. japonica may have decreased susceptibility to this cancer, though further sampling will be needed to confirm this hypothesis. We further developed a sensitive environmental DNA (eDNA) assay, targeting somatic mutations in the MarBTN mitogenome. Using this assay, we surveyed 51 sites throughout Puget Sound, detecting cancer at high levels at sites where MarBTN-positive clams were observed and in the surrounding area. These results identify a severe outbreak of transmissible cancer in a hybridizing population, due to transfer of disease from another ocean, and demonstrate the utility of eDNA methods to track BTN through the environment.